Upaya Penyelesaian Konflik Kepemilikan Tanah Warga Di Wilayah X - Nefri, Johan Edi; Ngimadudin, Ngimadudin (Hutanasyah : Jurnal Hukum Tata Negara, 2022)
This study attempts to review a phenomenon that occurred in the city of X regarding land conflicts, the beginning of the conflict a resident cut down a tree in the land owner's area, but when asked for clarification the woodcutter admitted that the land belonged to him, hence the beginning of the conflict. the purpose of this research is to provide literacy to the community so as not to get involved in excessive land ownership conflicts and provide literacy to the community so that the research method carried out by qualitative research researchers with a case study approach to readers about the importance of maintaining land rights ownership by completing all forms of ownership administration. The results of the study showed that the defendant was not doing the law by cutting down trees that did not belong to him for the ownership of the land